Acute Kidney Injury in Pregnant Patient With Pancreas-Kidney Transplant Caused by Abdominal Compartment Syndrome: A Case Presentation, Review of Literature, and Proposal of Diagnostic Approach. Issue 1 (July 2019) - Michalska, Magdalena; Wen, Kevin; Pauly, Robert P.
Rationale: With increasing number of complex medical patients with renal transplant who get pregnant, clinicians need to be aware of abdominal compartment syndrome which may masquerade as acute renal allograft injury in pregnancy. Presenting concerns of the patient: A 34-year-old nulliparous Caucasian female with end-stage renal disease (ESRD) due to type 1 diabetes mellitus who received a simultaneous pancreas-kidney transplant (SPK) in 2006 and then after rejection of renal allograft another, kidney-only allograft from a donation after circulatory death became pregnant in May 2013 with dichorionic, diamniotic twins without reproductive technology, and during pregnancy, she developed two episodes of acute injury to the renal allograft. Diagnoses: End-stage renal disease secondary to type I diabetes, acute renal allograft injury, tacrolimus toxicity, abdominal pain. Interventions (including prevention and lifestyle): She received intravenous hydration, medications contributing to renal failure were held, and pain and nauseas were controlled appropriately. Abdominal compartment syndrome was managed by maintaining intravascular pressure and optimizing regional and systemic vascular perfusion by appropriate fluid balance, evacuating intraluminal contents by decompressing gastrointestinal system, and improving abdominal wall compliance by using appropriate analgesics, sedation, and patient positioning. Outcomes: With advancing pregnancy, the patient developed progressive abdominal pain, nausea, leg edema, and rising creatinine that were not responsive to ongoing therapies and required delivery via Cesarean section at 31 weeks of gestational age. Lessons learned: In the era of increasing number of pregnant renal transplant patients with multiple medical issues, we need organized approach to diagnosis of acute renal allograft injury in pregnancy and we need to consider abdominal compartment syndrome as one of the causes.